2019
DOI: 10.1111/hex.12884
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient‐centred care for persons with Parkinson's: Qualitative interviews with care partners about their engagement in discussions of “off” periods

Abstract: Objective This study explored how care partners (CPs) of persons with Parkinson's (PwP) are engaged in discussions of “off” symptoms. Methods During qualitative interviews, CPs of PwP sampled by convenience through the Michael J Fox Foundation online clinical trial matching service were asked to describe their familiarity with “off” symptoms, how “off” symptoms were discussed with clinicians, and the impact of “off” symptoms on them. Data were analysed using constant comparative technique by all members of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…It is interesting that a higher proportion of carepartners reported recalling discussion of all aspects of OFF periods than patients, suggesting incomplete recall on the part of more patients and supporting the value of carepartner involvement. Our qualitative interviews also support the perceived value of carepartner input by all parties and the desire for carepartners to be part of the discussion (16). It was clear from those interviews, however, that they are often not included in the conversation.…”
Section: Discussionsupporting
confidence: 64%
“…It is interesting that a higher proportion of carepartners reported recalling discussion of all aspects of OFF periods than patients, suggesting incomplete recall on the part of more patients and supporting the value of carepartner involvement. Our qualitative interviews also support the perceived value of carepartner input by all parties and the desire for carepartners to be part of the discussion (16). It was clear from those interviews, however, that they are often not included in the conversation.…”
Section: Discussionsupporting
confidence: 64%
“…Although the reduction in symptoms was something she enjoyed, she reported feeling certain social distance from people who had not experienced undergoing DBS. Nevertheless, the improvement in PD symptoms did not led her to experience radical adjustment problems or behavioral changes negatively affecting her as shown in other studies [50,52,69].…”
Section: Discussionsupporting
confidence: 63%
“…The FCs (especially in the case of spouses) are not only emotionally involved in the illness of their loved ones, but they also provide care at home. Not only do they need to learn to manage the internal impact on their lives that the fact that their spouses have a chronic illness has, in most cases, they also adapt their routines to assist their loved ones in different tasks, such as helping with personal care and hygiene, managing the patient’s treatment, or organizing medical appointments [ 50 , 52 , 69 ]. In most cases, they are a great source of support and understanding for patients [ 49 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address symptom-related disabilities of PD, design guidelines for touch screen gestures have been suggested [ 55 ], as well as calibration of touch screen sensitivity [ 56 ]. Previous research also emphasizes the important role of informal caregivers in supporting self-care and symptom assessments [ 57 , 58 ]. Acknowledging caregivers’ role in self-care, it has been suggested that eHealth services for PD should be designed to support collaboration between PwP and their informal caregivers [ 59 ].…”
Section: Discussionmentioning
confidence: 99%